Single crystal cobalt-free positive electrode material, preparation method and lithium ion battery

By using bromide flux in a single crystal cobalt-free cathode material to form a structure of a core and bromide coating, the problem of poor performance of existing materials is solved, and the cycle stability and rate performance are significantly improved.

CN115799514BActive Publication Date: 2025-03-25SVOLT ENERGY TECH (WUXI) CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211655564.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-22
Publication Date
2025-03-25
Estimated Expiration
2042-12-22

AI Technical Summary

Technical Problem

The existing single-crystal cobalt-free cathode materials have poor performance and insufficient cycle stability and rate performance.

Method used

Bromide is used as flux to prepare a single crystal cobalt-free positive electrode material through flux growth method to form a structure of a core and a bromide coating layer, and the mass proportion of bromide is 1 to 10%.

Benefits of technology

The cyclic stability and rate performance of single-crystal cobalt-free cathode material is improved, the resistance to electrolyte is enhanced, unnecessary side reactions are reduced, and the structural stability of the material is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115799514B_ABST
    Figure CN115799514B_ABST
Patent Text Reader

Abstract

The present invention discloses a single crystal cobalt-free positive electrode material, a preparation method and a lithium ion battery; wherein a single crystal cobalt-free positive electrode material comprises a core and a bromide coating layer coated on the surface of the core, the core is doped with bromide, and the mass proportion of bromide in the single crystal cobalt-free positive electrode material is 1-10%; the present invention solves the problem of poor performance of existing single crystal cobalt-free positive electrode materials, and obtains a single crystal cobalt-free positive electrode material with better cycle stability and rate performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of lithium-ion batteries, and in particular to a single-crystal cobalt-free positive electrode material, a preparation method and a lithium-ion battery. Background Art

[0002] Ternary cathode materials have attracted more and more attention from researchers due to their high energy density. Compared with traditional polycrystalline ternary cathode materials, single-crystal ternary cathode materials have attracted widespread attention in the field of lithium-ion batteries due to their higher mechanical strength, energy density and better cycle performance. However, the currently commonly used single-crystal ternary cathode materials all contain cobalt, which increases their cost and pollution, and restricts their development to a certain extent. As a new type of cathode material, single-crystal cobalt-free cathode materials have the advantages of single crystalization and reduce cost and pollution. However, it is not simple to synthesize single-crystal cobalt-free cathode materials, especially nickel-rich materials. The current conventional method is to prepare single-crystal cobalt-free cathode materials by high-temperature synthesis, such as a spinel-type single-crystal cobalt-free high-voltage lithium nickel manganese oxide cathode material, its preparation method and lithium-ion battery disclosed in Chinese patent CN113178566A. However, the increase in sintering temperature will lead to mixed cations and irregular particle shape and size, resulting in the material being significantly poor in various performance indicators such as cycle performance and rate performance.

[0003] As a new type of synthesis method for single crystal positive electrode materials, the flux growth method is conventionally used in cobalt-containing single crystal ternary positive electrode materials, and in the preparation process it often only has a single effect of lowering the sintering temperature. In order to avoid the incorporation of impurity elements and thus ensure the performance of the ternary positive electrode material, it is usually necessary to use a water washing step in the subsequent steps to remove them, resulting in a complicated preparation process and poor performance of the prepared single crystal cobalt-free positive electrode material. Summary of the invention

[0004] Therefore, the purpose of the present invention is to solve the problem of poor performance of existing single crystal cobalt-free positive electrode materials and to provide a single crystal cobalt-free positive electrode material, a preparation method and a lithium ion battery with better cycle stability and rate performance.

[0005] A single crystal cobalt-free positive electrode material comprises a core and a bromide coating layer coated on the surface of the core, wherein the core is a bromide-doped single crystal cobalt-free positive electrode material, and the mass proportion of bromide in the single crystal cobalt-free positive electrode material is 1-10%.

[0006] The D50 of the single crystal cobalt-free positive electrode material is 1-4 μm, and the thickness of the bromide coating layer is ≤100 nm. Preferably, the D50 of the single crystal cobalt-free positive electrode material is 3-4 μm, and the thickness of the bromide coating layer is ≤20 nm.

[0007] The ionic conductivity of the single crystal cobalt-free cathode material is 10-8 ~10 -3 S / cm, electronic conductivity is 10 -6 ~10 - 2 S / cm, the ion diffusion coefficient is 10 -13 ~10 -6 cm 2 / s; Preferably, the ionic conductivity of the single crystal cobalt-free positive electrode material is 10 -4 ~10 -3 S / cm, electronic conductivity is 10 -4 ~10 -3 S / cm, the ion diffusion coefficient is 10 -10 ~10 -9 cm 2 / s;

[0008] And / or, the intensity ratio of the 003 X-ray diffraction peak to the 104 X-ray diffraction peak of the single crystal cobalt-free positive electrode material is ≥1.5, and the half-peak width of the 003 X-ray diffraction peak is 0.4° to 1.0°; preferably, the intensity ratio of the 003 X-ray diffraction peak to the 104 X-ray diffraction peak of the single crystal cobalt-free positive electrode material is ≥1.6, and the half-peak width of the 003 X-ray diffraction peak is 0.4° to 0.7°;

[0009] And / or, the specific surface area of ​​the single crystal cobalt-free positive electrode material is 0.01 to 2 m 2 / g, pH value ≤ 11.5; preferably, the specific surface area of ​​the single crystal cobalt-free positive electrode material is 0.08 to 0.1 m 2 / g;

[0010] And / or, the single crystal cobalt-free positive electrode material is LiNi x M 1-x O2, 0.6≤x≤0.95; M is one of Mn and Al.

[0011] A method for preparing a single crystal cobalt-free positive electrode material, comprising:

[0012] A Ni-M-based precursor is mixed with a lithium source to obtain a mixed powder a, wherein M is at least one of Mn and Al;

[0013] Mixing the mixed powder a with the bromide to obtain a mixed powder b; the mass proportion of the bromide in the mixed powder b is 1 to 10%;

[0014] The mixed powder b is heated to 450-500°C at a heating rate of 2-10°C / min under an oxygen atmosphere and kept warm for 2-3 hours; then the temperature is raised to 800-900°C at a heating rate of 1-3°C / min and kept warm for 10-16 hours. After cooling, a single crystal cobalt-free positive electrode material is obtained.

[0015] The Ni-M based precursor is Ni x M 1-x (OH)2, M is one of Mn or Al, wherein 0.6≤x≤0.95.

[0016] The molar ratio of the Ni-M based precursor to the lithium source is 1:1.06-1.15.

[0017] The lithium source is one of lithium hydroxide, lithium carbonate, lithium nitrate and lithium oxalate, preferably lithium carbonate.

[0018] The bromide is at least one of potassium bromide, sodium bromide, magnesium bromide and lithium bromide.

[0019] The preparation process of the mixed powder b also includes the step of mixing a halide flux into the mixed powder a; the halide flux is at least one of potassium fluoride, sodium fluoride, magnesium fluoride, lithium fluoride, potassium chloride, sodium chloride, magnesium chloride, and lithium chloride; the mass proportion of the halide flux in the mixed powder b is 1 to 5%.

[0020] A lithium-ion battery comprises the above-mentioned single crystal cobalt-free positive electrode material, or a single crystal cobalt-free positive electrode material prepared by the above-mentioned single crystal cobalt-free positive electrode material preparation method.

[0021] The technical solution of the present invention has the following advantages:

[0022] 1. A single crystal cobalt-free cathode material of the present invention comprises a core and a bromide coating layer coated on the surface of the core, wherein the core is a bromide-doped single crystal cobalt-free cathode material, and the mass proportion of bromide in the single crystal cobalt-free cathode material is 1-10%; the anions and cations in the bromide of the present invention can be doped into the interior of the matrix, and the Br in the bromide - Doping resists the corrosion of hydrogen fluoride from the electrolyte and strengthens the Br- and metal bonds, thus improving the integrity of the interface between the positive electrode and the electrolyte; in addition, the cation doping in the bromide can also occupy the Li site, expand the interlayer spacing, thereby increasing the diffusion rate of Li+ and further improving the rate performance of the single crystal cobalt-free positive electrode material. At the same time, the surface of the core is also coated with a halide coating layer, which can effectively prevent the direct contact between the material and the electrolyte and improve the structural stability of the material;

[0023] Therefore, the single crystal cobalt-free positive electrode material prepared by the present invention has significantly improved cycle stability and rate performance compared with conventional single crystal cobalt-free positive electrode materials.

[0024] 2. The present invention provides a method for preparing a single crystal cobalt-free positive electrode material, which only requires the use of bromide as a flux, which is added to a Ni-M-based precursor and a lithium source to obtain a mixed powder a for sintering once, and no water washing is required after sintering. In the preparation process, the flux not only acts as a flux to reduce the preparation temperature of the single crystal cobalt-free positive electrode material, but also in the process of preparing the single crystal cobalt-free positive electrode material, the anions and cations in the bromide can also be doped into the interior of the matrix, thereby preparing a single crystal cobalt-free positive electrode material with a bromide-doped single crystal cobalt-free positive electrode material as the core and bromide coated on the surface of the core;

[0025] Therefore, in the preparation process of the present invention, the bromide not only acts as a flux to promote the growth of cobalt-free single crystal positive electrode particles and reduce the calcination temperature. On the other hand, anion and cation co-doping can also be achieved in situ, which not only enhances the ability to resist hydrogen fluoride corrosion in the electrolyte, but also expands the interlayer spacing to increase the lithium ion diffusion rate, thereby improving the rate performance of the single crystal cobalt-free positive electrode material. In addition, the coating layer can reduce the surface residue of excess lithium salt and prevent direct contact between the electrolyte and the material, thereby reducing unnecessary side reactions, preventing the growth of the CEI film and improving the structural stability of the single crystal cobalt-free positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0027] Figure 1 SEM image of the single crystal cobalt-free cathode material in Example 1;

[0028] Figure 2 TEM image of the single crystal cobalt-free cathode material in Example 1;

[0029] Figure 3 XPS graphs of Br 3d collected after etching to 0, 60 and 120 nm in Example 1;

[0030] Figure 4 This is a comparison chart of the cycle performance of the single crystal cobalt-free positive electrode materials prepared in Example 1 and Comparative Example 1;

[0031] Figure 5 This is a comparison chart of the rate performance of the single crystal cobalt-free positive electrode materials prepared in Example 1 and Comparative Example 1. DETAILED DESCRIPTION

[0032] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the guidance of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0033] If no specific experimental steps or conditions are specified in the examples, the experiments can be carried out according to the conventional experimental steps or conditions described in the literature in the art.

[0034] Example 1

[0035] A method for preparing a single crystal cobalt-free positive electrode material, the specific process of which is as follows:

[0036] (1) Ni 0.8 Mn 0.2 (OH)2 and lithium carbonate are ground in a molar ratio of 1:1.08 to obtain a mixed powder a;

[0037] (2) Mixed powder a and magnesium bromide (MgBr2) are completely mixed and ground evenly, and the resulting powder is marked as mixed powder b. The mass ratio of flux in mixed powder b is controlled to be 4%;

[0038] (3) then heating the mixed powder b to 500° C. at a heating rate of 5° C. / min and keeping the temperature for 3 h in an oxygen atmosphere, then heating the mixed powder b to 850° C. at a heating rate of 2° C. / min and keeping the temperature for 14 h, and then cooling the mixed powder b to obtain powder particles;

[0039] (4) The powder particles are crushed and sieved to obtain a single crystal cobalt-free positive electrode material LiNi 0.8 Mn 0.2 O2.

[0040] The single crystal cobalt-free positive electrode material LiNi prepared in this embodiment 0.8 Mn 0.2 O2 was used for SEM and TEM detection, and the obtained positive electrode material was etched to obtain the XPS graphs of Br 3d after etching to 0, 60 and 120 nm, respectively. Figure 1-3 As shown. Figure 1 The SEM scanning electron microscopy results show that the obtained product is a single crystal particle with a smooth surface and no impurities, and the particle size is 2μm-4μm. Figure 2 The TEM results in Figure 2 show that the surface of the particles is covered with a layer of halide. Figure 3 The XPS results show that Br ions are doped into the interior of the particles.

[0041] Example 2

[0042] A method for preparing a single crystal cobalt-free positive electrode material, the specific process of which is as follows:

[0043] (1) Ni 0.8 Mn 0.2 (OH)2 and lithium carbonate are ground in a molar ratio of 1:1.08 to obtain a mixed powder a;

[0044] (2) Mixed powder a and potassium bromide (KBr) are completely mixed and ground evenly, and the resulting powder is marked as mixed powder b. The mass ratio of flux in mixed powder b is controlled to be 4%;

[0045] (3) then heating the mixed powder b to 500° C. at a heating rate of 5° C. / min and keeping the temperature for 3 h in an oxygen atmosphere, then heating the mixed powder b to 850° C. at a heating rate of 2° C. / min and keeping the temperature for 14 h, and then cooling the mixed powder b to obtain powder particles;

[0046] (4) The powder particles are crushed and sieved to obtain a single crystal cobalt-free positive electrode material LiNi 0.8 Mn 0.2 O2.

[0047] Example 3

[0048] A method for preparing a single crystal cobalt-free positive electrode material, the specific process of which is as follows:

[0049] (1) Ni 0.8 Mn 0.2 (OH)2 and lithium carbonate are ground in a molar ratio of 1:1.08 to obtain a mixed powder a;

[0050] (2) Mixed powder a and sodium bromide (NaBr) are completely mixed and ground evenly, and the resulting powder is marked as mixed powder b. The mass ratio of flux in mixed powder b is controlled to be 4%;

[0051] (3) then heating the mixed powder b to 500° C. at a heating rate of 5° C. / min and keeping the temperature for 3 h in an oxygen atmosphere, then heating the mixed powder b to 850° C. at a heating rate of 2° C. / min and keeping the temperature for 14 h, and then cooling the mixed powder b to obtain powder particles;

[0052] (4) The powder particles are crushed and sieved to obtain a single crystal cobalt-free positive electrode material LiNi 0.8 Mn 0.2 O2.

[0053] Example 4

[0054] A method for preparing a single crystal cobalt-free positive electrode material, the specific process of which is as follows:

[0055] (1) Ni 0.8 Mn 0.2(OH)2 and lithium carbonate are ground in a molar ratio of 1:1.08 to obtain a mixed powder a;

[0056] (2) Mixed powder a and lithium bromide (LiBr) are completely mixed and ground evenly, and the resulting powder is marked as mixed powder b. The mass ratio of flux in mixed powder b is controlled to be 4%;

[0057] (3) then heating the mixed powder b to 500° C. at a heating rate of 5° C. / min and keeping the temperature for 3 h in an oxygen atmosphere, then heating the mixed powder b to 850° C. at a heating rate of 2° C. / min and keeping the temperature for 14 h, and then cooling the mixed powder b to obtain powder particles;

[0058] (4) The powder particles are crushed and sieved to obtain a single crystal cobalt-free positive electrode material LiNi 0.8 Mn 0.2 O2.

[0059] Example 5

[0060] A method for preparing a single crystal cobalt-free positive electrode material, the specific process of which is as follows:

[0061] (1) Ni 0.6 Mn 0.4 (OH)2 and lithium nitrate are ground in a molar ratio of 1:1.13 to obtain a mixed powder a;

[0062] (2) Mixed powder a and magnesium bromide (MgBr2) are completely mixed and ground evenly, and the resulting powder is marked as mixed powder b. The mass ratio of flux in mixed powder b is controlled to be 1%;

[0063] (3) then heating the mixed powder b to 450° C. at a heating rate of 2° C. / min and keeping the temperature for 2 h in an oxygen atmosphere, then heating the mixed powder b to 900° C. at a heating rate of 3° C. / min and keeping the temperature for 10 h, and then cooling the mixed powder b to obtain powder particles;

[0064] (4) The powder particles are crushed and sieved to obtain a single crystal cobalt-free positive electrode material LiNi 0.6 Mn 0.4 O2.

[0065] Example 6

[0066] A method for preparing a single crystal cobalt-free positive electrode material, the specific process of which is as follows:

[0067] (1) Ni 0.9 Mn 0.1 (OH)2 and lithium hydroxide are ground in a molar ratio of 1:1.10 to obtain a mixed powder a;

[0068] (2) Mixing the mixed powder a with magnesium bromide (MgBr2) and grinding the mixed powder to obtain a uniform powder, and marking the obtained powder as mixed powder b. The mass ratio of the flux in the mixed powder b is controlled to be 10%;

[0069] (3) then heating the mixed powder b to 500° C. at a heating rate of 10° C. / min and keeping the temperature for 2.5 h in an oxygen atmosphere, then heating the mixed powder b to 800° C. at a heating rate of 1° C. / min and keeping the temperature for 16 h, and then cooling the mixed powder b to obtain powder particles;

[0070] (4) The powder particles are crushed and sieved to obtain a single crystal cobalt-free positive electrode material LiNi 0.9 Mn 0.1 O2.

[0071] Example 7

[0072] A method for preparing a single crystal cobalt-free positive electrode material, the specific process of which is as follows:

[0073] (1) Ni 0.95 Mn 0.05 (OH)2 and lithium carbonate are ground in a molar ratio of 1:1.10 to obtain a mixed powder a;

[0074] (2) Mixing the mixed powder a with magnesium bromide (MgBr2) and grinding the mixed powder to obtain a uniform powder, and marking the obtained powder as mixed powder b. The mass ratio of the flux in the mixed powder b is controlled to be 8%;

[0075] (3) Then, the mixed powder b was heated to 500° C. at a heating rate of 8° C. / min under an oxygen atmosphere and kept at that temperature for 2.5 h, then heated to 880° C. at a heating rate of 2° C. / min and kept at that temperature for 16 h, and then cooled to obtain powder particles;

[0076] (4) The powder particles are crushed and sieved to obtain a single crystal cobalt-free positive electrode material LiNi 0.95 Mn 0.05 O2.

[0077] Example 8

[0078] A method for preparing a single crystal cobalt-free positive electrode material, the specific process of which is as follows:

[0079] (1) Ni 0.8 Al 0.2 (OH)2 and lithium carbonate are ground in a molar ratio of 1:1.10 to obtain a mixed powder a;

[0080] (2) Mixing the mixed powder a with magnesium bromide (MgBr2) and grinding the mixed powder to obtain a uniform powder, and marking the obtained powder as mixed powder b. The mass ratio of the flux in the mixed powder b is controlled to be 5%;

[0081] (3) Then, the mixed powder b was heated to 500° C. at a heating rate of 5° C. / min in an oxygen atmosphere and kept at that temperature for 2.5 h, then heated to 840° C. at a heating rate of 2° C. / min and kept at that temperature for 12 h, and then cooled to obtain powder particles;

[0082] (4) The powder particles are crushed and sieved to obtain a single crystal cobalt-free positive electrode material LiNi 0.8 Al 0.2 O2.

[0083] Example 9

[0084] A method for preparing a single crystal cobalt-free positive electrode material, the specific process of which is as follows:

[0085] (1) Ni 0.8 Mn 0.2 (OH)2 and lithium carbonate are ground in a molar ratio of 1:1.08 to obtain a mixed powder a;

[0086] (2) Mixed powder a, magnesium bromide (MgBr2), and halide flux sodium chloride (NaCl) are completely mixed and ground evenly, and the resulting powder is marked as mixed powder b. The mass ratio of magnesium bromide in mixed powder b is controlled at 4%, and the mass ratio of sodium chloride in mixed powder b is controlled at 4%;

[0087] (3) then heating the mixed powder b to 500° C. at a heating rate of 5° C. / min and keeping the temperature for 3 h in an oxygen atmosphere, then heating the mixed powder b to 850° C. at a heating rate of 2° C. / min and keeping the temperature for 14 h, and then cooling the mixed powder b to obtain powder particles;

[0088] (4) The powder particles are crushed and sieved to obtain a single crystal cobalt-free positive electrode material LiNi 0.8 Mn 0.2 O2.

[0089] Comparative Example 1

[0090] A method for preparing a single crystal cobalt-free positive electrode material, the specific process of which is as follows:

[0091] (1) Ni 0.8 Mn 0.2 (OH)2 and lithium carbonate are ground in a molar ratio of 1:1.08 to obtain a mixed powder a;

[0092] (2) Mixing the mixed powder a with NaCl and grinding it evenly, the obtained powder is marked as mixed powder b, and the mass ratio of the flux in the mixed powder c is controlled to be 4%;

[0093] (3) then heating the mixed powder b to 500° C. at a heating rate of 5° C. / min and keeping the temperature for 3 h in an oxygen atmosphere, then heating the mixed powder b to 850° C. at a heating rate of 2° C. / min and keeping the temperature for 14 h, and then cooling the mixed powder b to obtain powder particles;

[0094] (4) The powder particles are crushed and sieved to obtain a single crystal cobalt-free positive electrode material LiNi 0.8 Mn 0.2 O2.

[0095] Comparative Example 2

[0096] A method for preparing a single crystal cobalt-free positive electrode material, the specific process of which is as follows:

[0097] (1) Ni 0.8 Mn 0.2 (OH)2 and lithium carbonate are ground in a molar ratio of 1:1.08 to obtain a mixed powder a;

[0098] (2) heating the mixed powder a to 500° C. at a heating rate of 5° C. / min and keeping the temperature for 3 h in an oxygen atmosphere, then heating the mixed powder a to 850° C. at a heating rate of 2° C. / min and keeping the temperature for 14 h, and then cooling the mixed powder a to obtain powder particles;

[0099] (3) The powder particles are crushed and sieved to obtain a single crystal cobalt-free positive electrode material LiNi 0.8 Mn 0.2 O2.

[0100] Test Example 1

[0101] The cathode material prepared by the embodiment and the comparative example is tested for its D50, coating thickness, ionic conductivity, electronic conductivity, ion diffusion coefficient, intensity ratio of 003X-ray diffraction peak to 104X-ray diffraction peak, half-peak width of 003X-ray diffraction peak, and specific surface area. Among them, D50 is detected by grid screening method, coating thickness is detected by projection electron microscope, ionic conductivity, electronic conductivity, and ion diffusion coefficient are all detected by Chenhua electrochemical workstation, intensity ratio of 003X-ray diffraction peak to 104X-ray diffraction peak, and half-peak width of 003X-ray diffraction peak are all detected by XRD, and specific surface area is detected by GB / T19587-2004 "Gas Adsorption BET Method for Determination of Specific Surface Area of ​​Solid Materials". The test results of the above items are shown in Tables 1 and 2 below.

[0102] Table 1

[0103]

[0104] Table 2

[0105]

[0106] Customer Case No. P20221956

[0107]

[0108] It can be seen from Tables 1 and 2 above that the single crystal cobalt-free positive electrode material prepared by the present invention has both a core and a bromide coating layer, and the core is also doped with bromide. Moreover, bromide doping can effectively improve ionic conductivity, electronic conductivity and ion diffusion coefficient.

[0109] Test Example 2

[0110] The positive electrode material prepared in the embodiment and the comparative example is applied to the battery. The assembly process of the battery is as follows: first weigh 0.2g of the positive electrode material, 0.025g of PVDF and 0.025g of graphite, put the three into a mortar at a mass ratio of 8:1:1 and grind them evenly for 40 minutes, then add 0.8ml of N-methyl-2-pyrrolidone (NMP) and stir continuously for 10 minutes to make the slurry free of particles, then evenly coat it on the aluminum foil with a scraper, and then put it into a blast drying oven and dry it at 100°C for 30min, take it out and cut it into a circular pole piece and aluminum sheet with a diameter of 12mm with a cutting machine, and put the two into a vacuum drying oven together and dry them at 60°C for 12h before taking them out, and weigh them with an electronic balance, and finally assemble the positive pole piece, lithium sheet, shrapnel, gasket, positive electrode shell, negative electrode shell, diaphragm and electrolyte in a glove box into a CR2025 type button half-battery.

[0111] The battery corresponding to the positive electrode materials of different embodiments and comparative examples was tested for cycle performance and rate performance, wherein the test results of embodiment 1 and comparative example 1 are as follows: Figure 4 and Figure 5 At the same time, the voltage of the battery corresponding to each embodiment and comparative example is in the range of 2.8-4.3V, customer case number P20221956

[0112] 1C(1C=200mA·g -1 ) after 200 cycles at a rate of 5C, as well as the discharge capacity data of each embodiment and comparative example at 5C, the results are shown in Table 3 below.

[0113] Table 3

[0114]

[0115] According to the above test results, the single crystal cobalt-free positive electrode material prepared by the present invention has a bromide-doped core and a bromide coating layer on the core surface. Compared with the single crystal cobalt-free positive electrode material without bromide doping and coating, it has obvious improvements in both the recapacity retention rate and the discharge capacity, effectively improving the cycle stability and rate performance of the single crystal cobalt-free positive electrode material.

[0116] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.

Claims

1. A single crystal cobalt-free positive electrode material, characterized in that: It comprises a core and a bromide coating layer coated on the surface of the core, wherein the core is doped with bromide, and the mass proportion of bromide in the single crystal cobalt-free positive electrode material is 1 to 10%; The single crystal cobalt-free positive electrode material is LiNi x M 1-x O2, 0.6≤x≤0.95; M is one of Mn or Al; The bromide is at least one of potassium bromide, sodium bromide, magnesium bromide and lithium bromide.

2. A single crystal cobalt-free positive electrode material according to claim 1, characterized in that: The D50 of the single crystal cobalt-free positive electrode material is 1-4 μm, and the thickness of the bromide coating layer is ≤100 nm.

3. A single crystal cobalt-free positive electrode material according to claim 1 or 2, characterized in that: The ionic conductivity of the single crystal cobalt-free cathode material is 10 -8 ~10 -3 S / cm, electronic conductivity is 10 -6 ~10 -2 S / cm, the ion diffusion coefficient is 10 -13 ~10 -6 cm 2 / s; And / or, the intensity ratio of the 003 X-ray diffraction peak to the 104 X-ray diffraction peak of the single crystal cobalt-free positive electrode material is ≥1.5, and the half-peak width of the 003 X-ray diffraction peak is 0.4° to 1.0°; And / or, the specific surface area of ​​the single crystal cobalt-free positive electrode material is 0.01 to 2 m 2 / g, pH value ≤11.

5.

4. A method for preparing a single crystal cobalt-free positive electrode material, characterized in that: include: A Ni-M-based precursor is mixed with a lithium source to obtain a mixed powder a, wherein M is at least one of Mn and Al; Mixing the mixed powder a with the bromide to obtain a mixed powder b; the mass proportion of the bromide in the mixed powder b is 1 to 10%; The mixed powder b is heated to 450-500°C at a heating rate of 2-10°C / min in an oxygen atmosphere and kept at this temperature for 2-3 hours; then the mixed powder b is heated to 800-900°C at a heating rate of 1-3°C / min and kept at this temperature for 10-16 hours, and a single crystal cobalt-free positive electrode material is obtained after cooling; The bromide is at least one of potassium bromide, sodium bromide, magnesium bromide and lithium bromide; The Ni-M based precursor is Ni x M 1-x (OH)2, M is one of Mn or Al, wherein 0.6≤x≤0.

95.

5. The preparation method according to claim 4, characterized in that: The molar ratio of the Ni-M based precursor to the lithium source is 1:1.06-1.

15.

6. The preparation method according to claim 4 or 5, characterized in that: The lithium source is one of lithium hydroxide, lithium carbonate, lithium nitrate and lithium oxalate.

7. The preparation method according to claim 6, characterized in that: The lithium source is lithium carbonate.

8. The preparation method according to claim 4 or 5, characterized in that: The preparation process of the mixed powder b also includes the step of mixing a halide flux into the mixed powder a; the halide flux is at least one of potassium fluoride, sodium fluoride, magnesium fluoride, lithium fluoride, potassium chloride, sodium chloride, magnesium chloride, and lithium chloride; the mass proportion of the halide flux in the mixed powder b is 1 to 5%.

9. A lithium ion battery, characterized in that: A single crystal cobalt-free positive electrode material comprising any one of claims 1 to 3, or a single crystal cobalt-free positive electrode material prepared by the method for preparing a single crystal cobalt-free positive electrode material according to any one of claims 4 to 8.

Citation Information

Patent Citations

  • Doping and coating modified nickel-rich ternary cathode material as well as preparation method thereof

    CN109755537A

  • Spinel type single-crystal cobalt-free high-voltage lithium nickel manganese oxide positive electrode material, preparation method thereof and lithium ion battery

    CN113178566A